Von Körpermärkten - Exenberger, Andreas; Nussbaumer, Josef (innsbruck university press, 2008)
"The valorization of the human body is of particular relevance in times of global market liberalization and reform debates on health systems. In one case, it is also about the often unabashed sale from the ""spare parts man"", the other is about the affordability of medical, often vital services. But all of this has a long history, from which one can draw conclusions for current debates and which we want to trace back to antiquity. We begin by discussing the increase in value through self-mutilation and the sale of human parts (with and without the consent of those affected), both of which show clear parallels to today's developments. We continue with the memory of younger (and also local) history, if we remember the treatment of mentally ill people in Tyrol a century and a half ago and the not so long history of transplantation medicine. This is followed by economic and bioethical explanations, which will be interesting, but not only for the insurance industry and reproductive medicine. Finally, there are two additional extras: the summary of the panel discussion, which was part of the symposium on ""Organknappheit? How to solve? ""And a compilation of different"" price lists ""for body and body parts over time. With contributions by Andreas Exenberger, Kordula Schnegg, Valentin Gröbner, Maria Heidegger, Marlene Hopfgartner, Andrea Leiter, Magdalena Thöni, Hannes Winner, Gabriele Werner-Felmayer, Matthias Stöckl and Josef Nussbaumer."